THE ESSENCE OF HUMANITY IN THE FIRST THREE VERSES OF SURAH AL-INSAN: A PHILOSOPHICAL EXEGESIS - Andi Dian Wulandari; Achmad Abubakar; Rahmi Damis; Andi Alfian (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2026)
This study departs from the question of how the Qur'an depicts humans not only as biological beings but also as beings with existential, epistemological, and moral dimensions. This study examines the nature of humans in verses 1–3 of surah al-Insan through a philosophical interpretation approach. The research aims to uncover the ontological, epistemological, and moral dimensions of humans in surah al-Insan verses 1–3. The method used is qualitative research with a library research type, employing a philosophical interpretation approach and content analysis techniques on the verses of the Qur'an and relevant Islamic interpretation and philosophy literature. The research results indicate that the essence of humans in surah al-Insan is understood as beings that originate from non-existence, thus being contingent and dependent on God as wajib al-wujud. Humans are also endowed with sensory and intellectual potential as the basis of knowledge, as well as the freedom to choose between gratitude and ingratitude accompanied by moral responsibility. In the view of Surah Al-Insan, humans are seen as beings who have biological existence as well as consciousness, rationality, and moral responsibility. This research contributes to enriching the study of Quranic exegesis through a philosophical approach to comprehensively understanding humanity's nature.